Female Urethral Reconstruction Using a Tubed Rectus Abdominis Myocutaneous Flap - Kozlow, Jeffrey H.; Chang, David W. (Journal of Reconstructive Microsurgery, 2012)
We describe the novel use of a rectus abdominis myocutaneous flap for reconstruction of the female urethra following an oncological pelvic resection. Reconstruction of the female urethra from the bladder neck to external urethral orifice was successfully performed, avoiding the need for a urostomy. To our knowledge, the myocutaneous flap has never been described for complete urethral reconstruction.
Keywords: VRAM; urethra reconstruction; cancer reconstruction